Alcohol‐ and drug‐related absenteeism: a costly problem - Ann Roche; Ken Pidd; Victoria Kostadinov (Elsevier, 2016)
Abstract Objective: Absenteeism related to alcohol and other drug (AOD) use can place a substantial burden on businesses and society. This study estimated the cost of AOD‐related absenteeism in Australia using a nationally representative dataset. Methods: A secondary analysis of the 2013 National Drug Strategy Household Survey (n=12,196) was undertaken. Two measures of AOD‐related absenteeism were used: participants' self‐reported absence due to AOD use (M1); and the mean difference in absence due to any illness/injury for AOD users compared to abstainers (M2). Both figures were multiplied by $267.70 (average day's wage in 2013 plus 20% on‐costs) to estimate associated costs. Results: M1 resulted in an estimation of 2.5 million days lost annually due to AOD use, at a cost of more than $680 million. M2 resulted in an estimation of almost 11.5 million days lost, at a cost of $3 billion. Conclusions: AOD‐related absenteeism represents a significant and preventable impost upon Australian businesses. Implications: Workplaces should implement evidence‐based interventions to promote healthy employee behaviour and reduce AOD‐related absenteeism.